Statistical Analysis of the Secondary Education Performance In Ukrainian Regions - A. Yu. Pashkovska (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2017)
The objective o f the study is analysis of the secondary education system in Ukrainianregion by use of cluster analysis. The following tasks are involved in the study: analysis o fthe secondary education performance in Ukrainian regions by the official statistics data; substantiation of the multidimensional grouping in analysis of the secondary education performance;multidimensional cluster analysis of the secondary education in Ukrainian regions.Analysis ofofficial statistics shows that Ukraine has featured downward tendency in thenumber of institutions of secondary education and, consequently, in the number of teachers.The main reasons behind this are the reducing numbers of population in the appropriate age, and mergers of some secondary schools to save material andfinancial resource.The analysis of data on secondary education for 2014/15 school year shows regionaldifferentiation of Ukraine, especially in funding of secondary education institutions andnumbers of students in private education institutions.Multidimensional clustering ofUkrainian regions is made by the following indicators: theamount ofpublic spending per pupil (XJ; the number of teachers per secondary school (XJ;the number of students per secondary school (XJ; the number o f secondary schools per 10,000 population (XJ; the number of students per teacher (XJ; the number of students per school of“new type” (XJ. Two clusters are built, each composed of two sub-clusters. A map of regionalzones in Ukraine as of 2014/15 school year, constructed by secondary education indicatorsincluded in the cluster analysis, is given. The study shows that cluster analysis can be aneffective tool to assess the secondary education performance at regional level in Ukraine.